Costs and economies of scale in repeated home-based HIV counselling and testing: Evidence from the ANRS 12249 Treatment as Prevention trial in South Africa. (July 2022) - Bousmah, Marwân-al-Qays; Iwuji, Collins; Okesola, Nonhlanhla; Orne-Gliemann, Joanna; Pillay, Deenan; Dabis, François; Larmarange, Joseph; Boyer, Sylvie; ,
Abstract: Universal HIV testing is now recommended in generalised HIV epidemic settings. Although home-based HIV counselling and testing (HB-HCT) has been shown to be effective in achieving high levels of HIV status awareness, little is still known about the cost implications of universal and repeated HB-HCT. We estimated the costs of repeated HB-HCT and the scale economies that can be obtained when increasing the population coverage of the intervention. We used primary data from the ANRS 12249 Treatment as Prevention (TasP) trial in rural South Africa (2012–2016), whose testing component included six-monthly repeated HB-HCT. We relied on the dynamic system generalised method of moments (GMM) approach to produce unbiased short- and long-run estimates of economies of scale, using the number of contacts made by HIV counsellors for HB-HCT as the scale variable. We also estimated the mediating effect of the contact quality – measured as the proportion of HIV tests performed among all contacts eligible for an HIV test – on scale economies. The mean cost (standard deviation) of universal and repeated HB-HCT was $24.2 (13.7) per contact, $1694.3 (1527.8) per new HIV diagnosis, and $269.2 (279.0) per appropriate referral to HIV care. The GMM estimations revealed the presence of economies of scale, with a 1% increase in the number of contacts for HB-HCT leading to a 0.27% decrease in the mean cost. Our results also suggested a significant long-run relationship between mean cost and scale, with a 1% increase in the scale leading to a 0.36% decrease in mean cost in the long run. Overall, we showed that significant cost savings can be made from increasing population coverage. Nevertheless, there is a risk that this gain is made at the expense of quality: the higher the quality of HB-HCT activities, the lower the economies of scale. Highlights: We estimated the costs of repeated home-based HIV counselling and testing (HB-HCT). The mean cost per new HIV diagnosis, which increased over HB-HCT rounds, was $1694. However, the mean cost per appropriate referral to HIV care was $269. A 1% increase in the scale of HB-HCT reduced the average cost per contact by 0.27%. Expanding the population coverage of HB-HCT offers opportunities for cost savings.